Invasive primary papillary carcinoma in a thyroglossal duct cyst: A case report and review of the literature - Loay M. Gertallah; Eman Eltokhy; Taha A. Baiomy; Ola A. Harb (Elsevier, 2019)
Patient: Female, 46. Clinical procedure: Sistrunk's procedure, Total Thyroidectomy and excision of the cervical lymph nodes. Background: Thyroglossal duct cyst is the commonest congenital anomaly of the thyroid gland. Occurrence of malignancy in a thyroglossal duct cyst is considered a rare condition, forming 1% of all cases of thyroglossal duct cyst. Here in the current report we presented a rare case of primary papillary carcinoma which arise in a thyroglossal duct cyst and a review of the literature. Case report: Our case is a 46-year-old female patient who presented with a painless cystic mass in front of the neck. After initial physical examination we have performed fine needle aspiration cytology (FNAC) of the cyst which revealed a papillary neoplasm. The patient underwent total thyroidectomy with excision of the cervical lymph nodes and surgical excision of the thyroglossal duct cyst (the Sistrunk's procedure). Histopathology of the specimen revealed a thyroglossal duct cyst which contains a primary invasive papillary carcinoma that infiltrated the cyst wall. The thyroid gland was normal, most of the cervical lymph node was positive for PTC. Conclusions: Primary papillary carcinoma of thyroglossal duct cyst is a rare condition that should be considered in patients with cystic midline neck masses. Surgery and radical excision is the optimal patient management to improve survival. Keywords: Papillary carcinoma, Thyroglossal duct cyst, Sistrunk's procedure, Thyroidectomy